2023
DOI: 10.1021/acs.energyfuels.3c00798
|View full text |Cite
|
Sign up to set email alerts
|

Minireview of Microscopic CO2 Interactions with Fluids and Minerals in Shale: Advances and Outlook

Abstract: Shale is featured by nanometer pores and ultralow permeability. Enhancing shale oil recovery after primary production is challenging as a result of the low injectivity of water. CO 2 could be a promising injection fluid to enhance shale oil recovery for its high mobility in porous media and mixability with hydrocarbons. Fluid behaviors in the nanometer pores of shale reservoirs deviate from those in the micrometer pores of conventional reservoirs. The previous understanding of CO 2 displacement and sequestrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…CO 2 injection into the formation will not only dissolve the formation minerals but also produce precipitation . Gunter et al predicted that alkaline aluminosilicate minerals in aquifers react with CO 2 and are decomposed into kaolinite, thereby neutralizing CO 2 .…”
Section: Co2 Storagementioning
confidence: 99%
“…CO 2 injection into the formation will not only dissolve the formation minerals but also produce precipitation . Gunter et al predicted that alkaline aluminosilicate minerals in aquifers react with CO 2 and are decomposed into kaolinite, thereby neutralizing CO 2 .…”
Section: Co2 Storagementioning
confidence: 99%
“…The higher the density of fractures, the diffusion was more obvious. In order to study the effect and mechanism of CO 2 huff and puff on improving shale oil recovery in fracture-matrix system, some scholars used a fracture-matrix model to study the effect of CO 2 huff and puff on improving shale oil recovery under different miscible pressures and used NMR technology to study the seepage characteristics of the fracture-matrix fluid in shale cores during CO 2 huff and puff. The results showed that the shale oil produced mainly came from large pores, while the effect of small pores was poor. , At present, most of the researches mainly focus on the CO 2 huff and puff recovery and injection parameters’ optimization . Few scholars have used the combined nuclear magnetic-physical modeling experimental means to reveal the mobilization law of crude oil in the microscopic pores during CO 2 huff and puff, the distribution law of residual oil after extraction, the characteristics of fluid exchange between matrix and fractures after hydraulic fracturing, and to quantitatively analyze the lower limit of pore size of the CO 2 huff and puff by means of different influencing factors from the pore structure of shale rock.…”
Section: Introductionmentioning
confidence: 99%
“…Tight gas reservoirs are currently a focal point in unconventional natural gas exploration and development, playing a pivotal role in natural gas production [1][2][3][4]. According to China's fourth oil and gas resource assessment, onshore tight gas resources in China total 21.85 × 10 12 m 3 , primarily concentrated in regions such as the Ordos Basin, Sichuan Basin, Songliao Basin, and Tarim Basin [5][6][7][8]. Notably, the Upper Paleozoic strata of the Ordos Basin account for 60% of these resources, totaling 13.32 × 10 12 m 3 [9].…”
Section: Introductionmentioning
confidence: 99%